Systemic β-Adrenergic Receptor Activation Augments the ex vivo Expansion and Anti-Tumor Activity of Vγ9Vδ2 T-Cells - Baker, Forrest L.; Bigley, Austin B.; Agha, Nadia H.; Pedlar, Charles R.; O'Connor, Daniel P.; Bond, Richard A.; Bollard, Catherine M.; Katsanis, Emmanuel; Simpson, Richard J. (Frontiers in Immunology, 2020)
TCR-gamma delta (γδ) T-cells are considered important players in the graft-versus-tumor effect following allogeneic hematopoietic cell transplantation (alloHCT) and have emerged as candidates for adoptive transfer immunotherapy in the treatment of both solid and hematological tumors. Systemic β-adrenergic receptor (β-AR) activation has been shown to mobilize TCR-γδ T-cells to the blood, potentially serving as an adjuvant for alloHCT and TCR-γδ T-cell therapy. We investigated if systemic β-AR activation, using acute dynamic exercise as an experimental model, can increase the mobilization, ex vivo expansion, and anti-tumor activity of TCR-γδ T-cells isolated from the blood of healthy humans. We also sought to investigate the β-AR subtypes involved, by administering a preferential β¬1-AR antagonist (bisoprolol) and a non-preferential β1 + β2-AR antagonist (nadolol) prior to exercise as part of a placebo controlled randomized cross-over design. We found that exercise mobilized TCR-γδ cells to blood and augmented their ex vivo expansion by ~182% compared to resting blood when stimulated with IL-2 and ZOL for 14-days. Exercise also increased the proportion of CD56, NKG2D+/CD62L-, and CD158a/b/e on expanded TCR-γδ cells, and increased their cytotoxic activity against several tumor target cells (K562, U266, 221.AEH) in vitro by 40-60%. Blocking NKG2D on TCR-γδ cells in vitro eliminated the augmented cytotoxic effects of exercise against U266 target cells. Furthermore, administering a β1 + β2-AR (nadolol), but not a β1-AR (bisoprolol) antagonist prior to exercise abrogated the exercise-induced enhancement in TCR-γδ T-cell mobilization and ex vivo expansion. Nadolol completely abrogated while bisoprolol partially inhibited the exercise-induced increase in the cytotoxic activity of the expanded TCR-γδ T-cells. We conclude that acute systemic β-AR activation in healthy donors markedly augments the mobilization, ex vivo expansion, and anti-tumor activity of TCR-γδ T-cells and that the majority of these effects are due to β2-AR signaling. These findings highlight β-ARs as potential targets to favorably alter the composition of allogeneic peripheral blood stem cell grafts and improve the potency of TCR-γδ T-cell immune cell therapeutics.